The psychology of learning and motivation - Ross, Brian H. (Psychology of learning and motivation, 2013)
The Psychology of Learning and Motivation series publishes empirical and theoretical contributions in cognitive and experimental psychology, ranging from classical and instrumental conditioning to complex learning and problem solving. Volume 58 of the highly regarded Psychology of Learning and Motivation seriesAn essential reference for researchers and academics in cognitive scienceRelevant to both applied concerns and basic research.